Implementation of the residual productivity principle in land valuing methods - Drapikovskyi, O.; Ivanova, I. (Land Management, Cadastre and Land Monitoring, 2020)
Land valuation is based on numerous principles, among which the principle of residual productivity plays a leading role. According to this principle, the current land value is determined by the residual income from its possible future use in the future, taking into account the costs and the time required to obtain this income. In addition, the residual productivity principle is fundamental in revealing the immanent uncertainty of land valuation due to the multiplicity of its value, each of which will be true in assumptions and false in other cases.The application of this principle in the land valuation has become constitutional in the formation and development of its methodological apparatus.The article discusses the evolution of land valuation methods based on the residual productivity principle – from traditional extraction methods and residual capitalization to discounted cash flow methods – and analyzes the main advantages and limitations of their use in valuation practice. The necessity of moving from deterministic to stochastic cash flows models and supplementing them with optional pricing models, which best reflect the modern understanding of the residual nature of land value and taking into account its inherent uncertainty, has been proved.Keywords: residual land productivity, uncertainty, deterministic and stochastic cash flow models, optional pricing models.